Strengthening Muslim Family Faith and the Importance of Da'wah in the Digital Age: Insights from Scholars of Al-Aziziyah Samalanga through the Lens of Islamic Philosophy - M. Amin, Syarkawi; Hanafiah, Mahmudi; Sabirin, Muhammad Iqbal; Zalikha, Siti; Hadi, Musafirul (El-Usrah: Jurnal Hukum Keluarga, 2025)
The advancement of technology in the era of the Industrial Revolution 4.0 has significantly expanded access to Islamic knowledge; however, it simultaneously presents challenges related to the imbalance between technological utilization and the reinforcement of the Islamic faith. This study addresses the core issue of Muslim family faith resilience and the critical need for digital da'wah, as perceived by scholars from Al-Aziziyah Islamic Boarding School. Employing a qualitative methodology grounded in Islamic philosophical theory, data were collected through in-depth interviews with key informants, including boarding school leaders, educators, and students. Complementary literature was reviewed from journals, books, and scientific reports. The research was conducted at Dayah Jamiah Al-Aziziyah in Samalanga, Bireuen, Aceh. Findings indicate that strengthening the resilience of aqidah within Muslim families involves multiple strategies, such as leveraging technology and social media as platforms for Islamic learning, alongside maintaining traditional religious instruction through regular taklim assemblies led by teachers and ulama. The boarding school, as a traditional educational institution, plays a pivotal role in effectively disseminating Islamic teachings via social media and online platforms. Furthermore, fortifying aqidah entails rigorous supervision of technology use, effective time management, verification of information, and collaborative efforts among the boarding school, families, and communities, with Al-Aziziyah Samalanga serving as a central hub. From the perspective of the Islamic philosophy, which prioritizes truth and the principles rooted in divine revelation as the ultimate reality, these efforts align with the beneficial aspects of scientific and technological progress. This study contributes an Islamic philosophical framework emphasizing the urgent necessity of digital da'wah to sustain and strengthen the aqidah resilience of Muslim families in the contemporary digital era.